STUDY OF CARBONATION DURABILITY OF SEVERAL ETTRINGITE-ENRICHED PASTES - Chen, Bao; HORGNIES, MATTHIEU; Morin, Vincent; BOUMAAZA, MOUNA; Huet, Bruno; Gengembre, Edouard; Baco, Isabelle; KEVYN JOHANNES; Kuznik, Frederic (WIT Transactions on Engineering Sciences, 2019)
Recent reported materials of high energy density for thermochemical heat storage are mostly inorganic rare elements salts, such as SrBr2 and LaCl3. However, their wide use may be hindered due to the high material cost. An affordable cement-based compound, named ettringite, of which energy density (~500 kWh/m3) is comparable, and even higher, than rare elements salts and therefore attracts people’s sight. As an alkaline phase in hydrated cement pastes, ettringite could be carbonated by CO2 in the air. The change of this mineral structure upon carbonation could reduce its capacity to store energy. This phenomenon is known to be unstoppable until there is a complete depletion of reactants. Consequently, it is necessary to investigate the carbonation rate of ettringite-based materials for energy storage. In the present work, a large range of characterization methods – such as optical microscopy analysis, mercury intrusion porosimetry (MIP), X-ray fluorescence (XRF), X-ray diffraction (XRD), Thermogravimetric analysis (TGA) – have been carried out to analyse phase structure and phase assemblage. Three series of cement pastes containing different contents of ettringite were firstly prepared. Then, crushed samples of a size of 1‒2mm were exposed to an accelerated carbonation environment (composed of 1% CO2 by volume, and 90% relative humidity (RH) at 20°C and ambient pressure) for different durations. The results have highlighted that the carbonation of ettringite-based granules under set conditions went very fast. The XRD patterns confirmed that the calcium carbonates were vaterite and aragonite accompanied with gypsum. Moreover, a bigger content of ettringite seemed to yield a higher carbonation resistance and a less foamy structure.